Hot melt extrusion method for preparation of ibuprofen/sucroester WE15 solid dispersions: evaluation and stability assessment - Laila H. Emara, Fatma M. Abdelfattah, Nesrin F. Taha (Journal of Applied Pharmaceutical Science, 2017)
Low melting points Sucroesters (SEs) are used in hot-melt extrusion technology (HME). However, there are few literatures studying the effect of SEs on drug release and their storage stability. In this study, SEïƒ’ WE15 was proposed to prepare sustained-release solid dispersions with Iburpofen (IBU), containing 60 & 30% w/w, by HME, fusion method and compared to physical mixtures. The fresh and stored samples were evaluated by a well-established release rate study (USP Apparatus IV), DSC and XRD. Results revealed that HME technique succeeded to produce sustained-release patterns for IBU. Stored samples (6 months at 40ï‚°C / 75 % RH) were unstable and showed gradual decrease in IBU release rate for both IBU loadings. HME formula (60% w/w IBU) showed an increase in the amount of drug released. Long term stability, one year at room temperature, showed a marked increase in IBU release rate for both drug loadings. Only HME containing 30% w/w IBU gave stable form among others. DSC and XRD suggested that increase of SE content led to almost complete IBU dissolved in this carrier, and considerable decrease in IBU release rate. This has been proven by DSC and XRD data analysis for IBU and SE (enthalpy and counts).
Keywords: Solid Dispersion, Hot Melt Extrusion, Sucroester® WE15, Stability,Ibuprofen.